Metadiscourse Analysis in Essays on the Hagia Sophia Reconversion - Wikasmara, Pranata; Shartika, Mira (Journal of Literature, Linguistics, & Cultural Studies, 2024)
This study investigated the use of metadiscourse markers in essays discussing the reconversion of Hagia Sophia from a museum to a mosque. By analyzing various essays, the research aimed to identify the most commonly used metadiscourse markers to understand how they contribute to the clarity and strength of the arguments presented using the qualitative method and Hyland's metadiscourse markers (2005). The findings revealed that interactive markers, such as transitions and frame markers, were widely used and effectively helped organize discourse in the essays. Meanwhile, interactional markers, such as hedging and boosters, were frequently employed to engage readers and emphasize key points. Additionally, the study found that authors supporting the reconversion of Hagia Sophia used metadiscourse to reinforce historical and religious narratives, while opponents focused on cultural heritage and secularism. The analysis of this study showed that metadiscourse shaped public discourse on controversial issues. The study also highlighted the significant role of metadiscourse in enhancing academic writing and suggests further research into multilingual and digital discourse contexts. Such research could provide more comprehensive insights into effective communication strategies, especially in discussions of globally significant and controversial issues. The study concluded that metadiscourse is essential for strengthening arguments and clarifying the author's position in sensitive and complex public debates, making it highly relevant in modern communication.